The Social Service For Elderly People on Village Community Service Based - Irmawan Irmawan (Jurnal Penelitian Kesejahteraan Sosial, 2017)
The longer life-time expectancy is one of indicators of national development success. Yogyakarta Special Region elderly people has a life-time expectancy of 74 years old and it is the highest in Indonesia. The length of life-time expectancy brings some impact on the growth of elderly people number in Yogyakarta. It is 12.6 percent of the total population there. Thiscondition is bringing some consequences in providing social services to the elderly people so that they can live a happy and healthy life indeed. This research is aimed to comprehend the existing social service for elderly people on village community service basis. The research was conducted at Dusun Prenggan, Sidomulyo Village, Bambanglipuro Sub-District, Bantul District, in Yogyakarta Province. The subjects of this research are social organization activists, public figures as social volunteers and the objects are social service activities for elderly people. Data collection techniques used: 1) directinterviews with the board of social organizations and members and community leaders, 2) Observation of social services activities, 3) Documents review. The result of the research showed that elderly people received various social services such as feeding, providing free medical examination, involving elderly people for gymnastics, giving spiritual guidance, praying and encouraging them in participating in traditional arts activities (such as kethoprak, slapstick and mocopatan), conducting any small travelling, handing over Eid gifts, doing some house renovations, visiting them for any sickness reasons or mourning reasons, providing trees to plant such as bananas, papaya, and asking for their contribution in raisingSocial Welfare Fund for any social solidarity. Concluded from the result of the research, it is recommended some points as follow: The Ministry of Social RI is expected to provide assistance to Social Organizations (orsos), NGOs, Communities that provide social services for the elderly people and the local government, social institutions, companies (through CSR program) are expected to empower communities and families to provide social services for the elderly people.